Responsiveness and Minimal Important Changes of the Western Ontario and McMaster Universities Osteoarthritis Index in Subjects Undergoing Rehabilitation Following Hip Fracture. (May 2017) - Monticone, Marco; Ambrosini, Emilia; Secci, Claudio; Rocca, Barbara; Ferrante, Simona; Capone, Antonio
Abstract : Objective: To evaluate the responsiveness and minimal important changes (MICs) for the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and its subscales in subjects with hip fractures. Design: At the beginning and end of a 2-month rehabilitation program, 106 patients completed the WOMAC. After the program, the global perceived effect (GPE) was analyzed to produce a dichotomous outcome (improved vs. stable). Responsiveness for the WOMAC and its subscales were calculated by distribution (effect size; standardized response mean) and anchor-based methods (receiver operating characteristic curves; correlations between change scores of the WOMAC and its subscales and GPE). Receiver operating characteristic curves were also used in order to compute the best cutoff levels between improved and stable subjects (MICs). Results: The effect size ranged from 0.64 to 11.10 and the standardized response mean from 0.79 to 2.65. The receiver operating characteristic analyses revealed an MIC value (area under the curve, sensitivity, specificity) for the WOMAC of 29 (0.817, 92, 78); values of 35 (0.820, 77, 76) 44 (0.625, 25, 95), and 24 (0.707, 100, 76) were found for pain, stiffness, and physical function subscales, respectively. Correlations between change scores of the WOMAC and its subscales and GPE were low (0.240, for stiffness subscale) to moderate (0.438–0.570 for the other subscales and the WOMAC). Conclusions: The WOMAC and its subscales (all but stiffness) were sensitive in detecting clinical changes in subjects with hip fracture undergoing rehabilitation. We recommend taking the MICs provided into account when assessing patients' improvement or planning studies in this clinical context.